2022
DOI: 10.1155/2022/3635989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhizobium Inoculation and P Fertilizer Levels on Selected Soil Properties, Yield, and Yield Components of Faba Bean (Vicia faba L.): The Case of Abuna Gindeberat, West Shewa Zone, Ethiopia

Abstract: Poor soil fertility status and inappropriate agronomic practices are the major factors for low crop productivity like legumes. Thus, the experiment was conducted to evaluate the effect of the P fertilizer rate and rhizobium inoculation on selected soil properties and yield of faba bean. In order to achieve this objective, a field experiment was laid out in a randomized complete block design in a factorial arrangement with replication. The treatments consisted of five P levels (0, 23, 46, 69, and 92 kg P2O5 ha−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This result in in line with the finding of [9] who reported that rhizobia isolate brought significance difference on nodulation number of faba bean when inoculated with faba bean seeds than the naturally existing rhizobacteriam in the soil. In the same manner, [6] (Chimdi A., et al, 2022) also reported that the maximum number of nodules per plant for 73.9 was recorded from the plots treated by strain Fb 18. The lowest nodule number per plant 97.73 was obtained when the seeds were inoculated with FB-EM-07.…”
Section: The Effects Of Different Faba Bean Rhizobia Isolates On Nodu...mentioning
confidence: 67%
“…This result in in line with the finding of [9] who reported that rhizobia isolate brought significance difference on nodulation number of faba bean when inoculated with faba bean seeds than the naturally existing rhizobacteriam in the soil. In the same manner, [6] (Chimdi A., et al, 2022) also reported that the maximum number of nodules per plant for 73.9 was recorded from the plots treated by strain Fb 18. The lowest nodule number per plant 97.73 was obtained when the seeds were inoculated with FB-EM-07.…”
Section: The Effects Of Different Faba Bean Rhizobia Isolates On Nodu...mentioning
confidence: 67%